ANALISIS PENGARUH INFLASI, PENANAMAN MODAL ASING DAN SUKU BUNGA TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA TAHUN 2000 – 2023 - Dwi Septi Cahyani -; Daryono Soebagiyo (Universitas Muhammadiyah Surakarta, 2025)
This study aims to analyze the effect of inflation, foreign investment, and interest rates on Indonesia's economic growth from 2000 to 2023. The data used in the study are secondary data and time series collected from various reliable official sources, including the Central Bureau of Statistics (BPS) and other relevant institutions. The analytical method used in this study is multiple linear regression with the Ordinary Least Square (OLS) approach to assess the research hypothesis. The results of this study state that inflation has a positive and significant influence on economic growth. In contrast, interest rate has a negative influence. Foreign direct investment does not show a significant effect on economic growth, although it remains important in the context of investment. The study concludes that long-term economic growth depends on stable inflation and adequate interest rate control.